The Diagnostic Role of Narrow-Band Imaging Bronchoscopy For Early Detection of Lung Adenocarcinoma in a Young Adult - Bu'ulolo, Christina Siuwandy; Semaraputra, Wayan Wahyu; Novitasari, Novitasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Lung adenocarcinoma is a common type of cancer that is typically associated with older individuals who have a history of smoking. However, in some rare cases, this occurs in young adults. Case: This case report discusses the diagnostic challenges and the important role of bronchoscopy in confirming lung adenocarcinoma in a 35-year-old male patient with a history of smoking. The patient had a persistent cough and unexplained weight loss. This raised concerns about various differential diagnoses, such as infectious diseases, abnormalities in the bronchial tree, and rare lung neoplasms. In this case report, we used a combination of White Light Bronchoscopy (WLB) and the Narrow Band Imaging (NBI) technique to identify pre-cancerous lesions and early-stage cancers within the airways. Discussion: This case report highlights the significance of bronchoscopy as a diagnostic tool for lung cancer in unexpected populations like young adults. The successful diagnosis through bronchoscopy led to prompt treatment initiation. Conclusion: This case underscores the importance of a multidisciplinary approach to lung cancer diagnosis and management, adapting to the unique situations of individual patients.